MEMS mass spectrometers: the next wave of miniaturization. (8th January 2016) - Syms, Richard R A; Wright, Steven
Abstract: This paper reviews mass spectrometers based on micro-electro-mechanical systems (MEMS) technology. The MEMS approach to integration is first briefly described, and the difficulties of miniaturizing mass spectrometers are outlined. MEMS components for ionization and mass filtering are then reviewed, together with additional components for ion detection, vacuum pressure measurement and pumping. Mass spectrometer systems containing MEMS sub-components are then described, applications for miniaturized and portable systems are discussed, and challenges and opportunities are presented.